The Impact of Different Writing Systems on Children’s Spelling Error Profiles: Alphabetic, Akshara, and Hanzi Cases - O’Brien, Beth A.; Habib Mohamed, Malikka Begum; Arshad, Nur Artika; Lim, Nicole Cybil (Frontiers in Psychology, 2020)
The importance of literacy in academics and the predominantly digital world cannot be understated. The literacy component of writing is less researched than that of reading, even though it holds equal significance for modern success. Spelling is an important aspect of the construct of literacy, and is more difficult to acquire than reading. Previous work on spelling error analysis for English provides insight into the sets of knowledge and cognitive processes required for children to perform the task, and their different strategies across development. However, different sets of skills and strategies may contribute to spelling across types of orthographies. In this study, we extend spelling error analysis to groups of biliterate children learning two scripts, which include English plus either: (a) another Latin-script alphabet with a shallow orthography (Malay); (b) a transparent alphasyllabary using akshara (Tamil); or (c) a non-alphabetic, morphosyllabic script using simplified hanzi characters (Mandarin Chinese). These sets of scripts vary in how speech is mapped to print. We utilized an error coding scheme based on triple-code theory to enumerate the occurrence of phonological, orthographic (graphemic), and morphological (semantic) types of spelling errors across the three language groups. Five hundred and sixty-eight Grade 1, 6-year-old children participated, with 128 English + Malay, 119 English + Tamil, and 321 English + Chinese children in each bilingual group. They completed a spelling to dictation task in their Asian language, with ten words taken from the grade level curriculum per language. Results indicate group differences in the proportions of error types, with more overall errors for Tamil, more phonological errors for Malay, and more irrelevant or nonsense words for Chinese. The implications are that different scripts present different challenges for young learners.